Regesten Kaiser Friedrichs III. (1440−1493), Heft 35 Die Urkunden und Briefe des Österreichischen Staatsarchivs in Wien, Abt. Haus-, Hof und Staatsarchiv: Allgemeine Urkundenreihe, Familienurkunden und Abschriftensammlungen (1480−1482) - Heinicker, Petra (2020)
The present volume lists 222 charters and letters of Emperor of the Holy Roman Empire, Frederick III. (1440-1493), issued between 1480 and 1482. The charters highlight sequences of political conflicts from the southwest to the northeast of the Empire, from Konstanz and Tyrol/Trento to Friesland and Riga, such as the replacement of the archbishop of Salzburg. Most of the charters and letters however serve to illustrate the more or less "regular" activities and official acts that were executed by Frederick III. as the local ruler of the Habsburgian hereditary territories.